Profil Diagnosa Keperawatan di RSUD Pasar Rebo - Melati Fajarini (Jurnal Persada Husada Indonesia, 2016)
Identifying the needs in nursing care in clinical practice is imperative to prepare expected competent graduated by the user. Nursing care are implemented based on the determined diagnosis. This study aimed to identify the profile of nursing diagnosis problems documented at RSUD Pasar Rebo in June 2015. The nursing diagnosis were identified from 144 in-patients’ medical records at 12 wards. Using proportional random sampling, 25 kinds of nursing diagnosis were documented but amongst 5 are excluded. The nurses documented 0-8 diagnosis per patient with the average 3 diagnosis per patient across wards. The data were analyzed from 367 diagnosis. The most frequent diagnosis are risk of infection (27%), risk/aktual deficient fluid volume (14%), and pain (11%). There is a need in further study of the nurses’ skills in determining nursing diagnosis. Educational institutions are challen88lged to prepare their students to be able to deliver nursing care especially the most frequent nursing diagnosis.